SAW Sensor with Langmuir-Blodgett Layer for Detection of Benzene and its Derivatives - Andrzej BALCERZAK; Piotr KIEŁCZYŃSKI; Marek SZALEWSKI; Krzysztof WIEJA (Archives of Acoustics)
Vapors of benzene and its derivatives are harmful and toxic for human beings and natural environment. Their detection has fundamental importance. For this purpose authors propose surface acoustic wave (SAW) sensor with skeletonized layer deposited by Langmuir-Blodgett (L-B) method. This layer was obtained by depositing a binary equimolar mixture of 5-[[1,3-dioxo-3-[4-(1-oxooctadecyl) phenyl]propyl]amino]–1,3–benzenedicarboxylic acid with cetylamine. The skeletonized sensor layer has been obtained by removing cetylamine. Response of this sensor depends mainly of the electrical dipole momentum of molecule. Among the tested compounds, benzene has a zero dipole moment and gives the smallest sensor response, and nitrobenzene has the largest dipole moment and the sensor reacts most strongly to its vapor.